2016
DOI: 10.1093/neuonc/now118
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular features of astroblastoma, includingBRAFV600Emutations, suggest an ontological relationship to other cortical-based gliomas of children and young adults

Abstract: Background. Astroblastomas (ABs) are rare glial tumors showing overlapping features with astrocytomas, ependymomas, and sometimes other glial neoplasms, and may be challenging to diagnose. Methods. We examined clinical, histopathological, and molecular features in 28 archival formalin-fixed, paraffinembedded AB cases and performed survival analyses using Cox proportional hazards and Kaplan-Meier methods. Results. Unlike ependymomas and angiocentric gliomas, ABs demonstrate abundant distinctive astroblastic pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 52 publications
9
67
1
Order By: Relevance
“…While this paper was under revision, Lehman et al . reported that 38% of analyzed ABs showed the BRAF V600E mutation, which strongly supports our data here.…”
Section: Discussionsupporting
confidence: 90%
“…While this paper was under revision, Lehman et al . reported that 38% of analyzed ABs showed the BRAF V600E mutation, which strongly supports our data here.…”
Section: Discussionsupporting
confidence: 90%
“…On reresection, his tumor was consistent with anaplastic ependymoma histologically and tested positive for MN1‐CXXC5 fusion. Given the presence of this alteration, the diagnosis was amended to astroblastoma, which are rare glial tumors histologically defined by astrocytic cells with broad thick processes arranged around blood vessels . Astroblastoma can be difficult to differentiate from ependymoma and other tumors with perivascular pseudorosettes.…”
Section: Resultsmentioning
confidence: 99%
“…These findings led to the review of molecular findings in histologically defined astroblastomas, a large proportion of which were shown to have MN1 alterations. The current understanding is that although astroblastoma histology is not specific to any particular tumor entity, a large number show MN1 alterations and cluster best with CNS high‐grade neuroepithelial tumors . A recent study of MN1‐altered tumors with astroblastoma histology showed good prognosis unlike that expected for PNET.…”
Section: Molecular Findings Leading To a Change In Histologic Diagnosismentioning
confidence: 98%
See 1 more Smart Citation
“…Further, the mutated cases can be potential candidates for targeted therapy. Recently, BRAF V600E mutation has also been documented in approximately 38% of cases of astroblastoma, which is a histomorphological entity as per WHO classification and have an unpredictable biological behavior . No hallmark genetic alteration associated with astroblastoma has been described till now.…”
Section: Discussionmentioning
confidence: 99%